Predisposing factors for candidemia in patients with major burns. Issue 2 (March 2015) - Fochtmann, Alexandra; Forstner, Christina; Hagmann, Michael; Keck, Maike; Muschitz, Gabriela; Presterl, Elisabeth; Ihra, Gerald; Rath, Thomas
Highlights We examined the occurrence of candidemia among patients with severe burns. In the present cohort we found a high candidemia incidence rate of 11%. An AIC based model selection procedure for logistic regression models was utilized. We identified gastrointestinal complications as independent risk factor for Candidemia. A prophylactic antifungal therapy in burn patients with gastrointestinal complications might be warranted.